Genesis of the Xifeng Low-Temperature Geothermal Field, Guizhou, SW China: Constrains From Geology, Element Geochemistry, and D-O Isotopes - Li, Yanyan; Dor, Ji; Zhang, Chengjiang; Wang, Guiling; Zhang, Baojian; Zhang, Fangfang; Xing, Yifei (Frontiers in Earth Science, 2021)
The Xifeng geothermal field is located in the Yangtze Craton, SW China, and is one of the most representative low-temperature geothermal fields in China. Widespread thermal anomalies, hot springs, and geothermal wells have been reported by previous studies. However, the nature and forming mechanisms of the field remain poorly understood. Element geochemical (ions, rare earth elements) and stable isotopic (D, O) composition of hot springs, geothermal fluids, rivers, and cold springs from different locations of the Xifeng geothermal field were analyzed in this study. The ions studies revealed that most samples featured the Ca-Mg-HCO3 type, except Xifeng hot springs, and which were characterized by the Ca-Mg-HCO3-SO4 type. Based on quartz geothermometers, the estimated reservoir temperature was 77°C. The results of stable isotopes (D, O) manifest that the Xifeng geothermal system was recharged by meteoric water at an elevation of 1,583 m from SW to NE. The research of rare earth elements (REE) revealed that their accumulation characteristics and obvious positive Eu anomaly were inherited from host feldspar-bearing reservoir dolomites through water-rock interactions. Combined with these observations, geological setting, and previous studies, it was concluded that the formation of the Xifeng geothermal field resulted from recharge, deep circulation, and secondary rising of the meteoric water along the faults. First, meteoric water infiltrated to depth through faults and crack zones. Second, the deep-infiltrated water was heated by radioactive heat, deep heat, and tectonic frictional heat. Finally, as the warmed-up waters underwent considerable deep circulation in the reservoir, it rose again along the main faults, and mixed with groundwater near the surface. Taken together, we suggest that the Xifeng geothermal system should be assigned as a faults-controlling, and deeply circulating meteoric water of low-temperature category.